Plug‐and‐Play Single‐Photon Devices with Efficient Fiber‐Quantum Dot Interface. Issue 10 (7th August 2022) - Jeon, Woong Bae; Moon, Jong Sung; Kim, Kyu‐Young; Ko, Young‐Ho; Richardson, Christopher J. K.; Waks, Edo; Kim, Je‐Hyung
Abstract: Incorporating solid‐state quantum emitters into optical fiber networks enables the long‐distance transmission of quantum information and the remote connection of distributed quantum nodes. However, interfacing quantum emitters with fiber optics encounters several challenges, including low coupling efficiency and delicate configuration. In this study, a highly efficient fiber‐interfacing photonic device that directly launches single photons from quantum dots into a standard FC/PC‐connectorized single‐mode fiber is demonstrated. Optimally designed photonic structures based on hole gratings produce an ultra‐narrow directional beam that matches the small numerical aperture of a single‐mode fiber. A pick‐and‐place technique precisely integrates a single miniaturized device into the core of the fiber. This approach realizes a plug‐and‐play single‐photon device that does not require optical alignment and thus guarantees long‐term stability. The results represent a major step toward practical and reliable transmission of quantum light across a fiber network. Abstract : In this paper, a practical and reliable plug‐and‐play single‐photon device based on hole‐based circular Bragg gratings is presented. The hole‐based circular Bragg grating with quantum dots produces an ultra‐narrow Gaussian beam that matches the small numerical aperture of a single‐mode fiber. This highly efficient fiber‐interfacing photonic device enables bright and stable single photons in an all‐fiber coupled channel from a source to a detector.